Regulierung trotz Nichtwissen Epistemisches Vertrauen als Handlungsressource und Methode im Recht - Blöcher, Johannes Robert (Mohr Siebeck, 2024)
It is not knowledge, but non-knowledge that determines modern regulatory practice. Legal practice can no longer understand technical phenomena such as blockchain and yet must still regulate them. Sociological theory teaches that modern regulation is only possible through trust in the information processing power of others when dealing competently with ones own non-knowledge.
PublicationDate: 20240628
Keywords: Soziales Handeln -- Rechtssoziologie -- Wissensgesellschaft -- (Anti)Szientismus -- Blockchain -- KI -- political rivalry -- Kryptowertpapiere -- Online-Register -- Rechtstheorie -- Besonderes Verwaltungsrecht -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht